Reversible cross-linked extruded profiles and methods

By using cross-linked extruded profiles formed by ethylene polymers and BiTEMPS methacrylate, the problem of difficult reuse or recycling of existing thermoset cross-linked polyolefin elastomers is solved by using the method of breaking disulfide bonds by heating, the problem of difficult reuse or recycling of existing thermoset cross-linked polyolefin elastomers is achieved, and the reprocessability and re-crosslinking of materials is improved, and the recyclability and durability are improved.

CN119546649APending Publication Date: 2025-02-28DOW GLOBAL TECHNOLOGIES LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380052915.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-15
Filing Date
2023-07-14
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing thermoset crosslinked polyolefin elastomers are difficult to reuse or recycle, limiting the recyclability and carbon neutrality of the material.

Method used

An ethylene polymer and 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate) are used as starting materials to form a crosslinkable extruded profile, and the disulfide bonds are broken at the reprocessing temperature to achieve reprocessing and re-crosslinking of the material.

Benefits of technology

Reprocessing and re-crosslinking of thermoset crosslinked polyolefin elastomers is realized, which improves the recyclability and durability of materials, and meets the needs of carbon neutrality and recyclability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119546649A_ABST
    Figure CN119546649A_ABST
Patent Text Reader

Abstract

The present disclosure provides an article of manufacture. In one embodiment, the article is an extruded profile comprised of a cross-linked composition formed from starting materials that include an ethylene-based polymer and a 2, 2, 6, 6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate). This results in an extruded profile consisting of a cross-linked composition comprising (i) an ethylene-based polymer, and (ii) a bond having structure 2. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Background Art

[0001] Thermosetting, cross-linked polyolefin elastomers are widely used in transportation and infrastructure applications such as automotive weatherproof seals and structures under the hood, hoses and belts. A conventional procedure for producing thermosetting cross-linked polyolefin elastomers is profile extrusion. In profile extrusion, polyolefin elastomers can form a network polymer with improved thermomechanical properties (such as compression set and creep resistance at high temperatures) via crosslinking of peroxides. Peroxide crosslinking forms a CC chemical bond, which is very stable and difficult to further dissociate by heating or mechanical shearing, thus limiting the reuse or recovery of post-industrial waste.

[0002] In light of global concerns regarding carbon neutrality and recyclability of plastic materials, the art recognizes the need for thermoset cross-linked extruded profiles that can be reprocessed and / or recycled. Summary of the invention

[0003] The present disclosure provides an article. In one embodiment, the article is an extruded profile composed of a crosslinked composition formed from a starting material comprising: an ethylene polymer and 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate). This produces an extruded profile composed of a crosslinked composition comprising (i) an ethylene polymer, and (ii) a bond having structure 2

[0004]

[0005] The present disclosure provides a method. In one embodiment, the method includes heating a first article to a reprocessing temperature, the first article consisting of an extruded profile, the extruded profile consisting of a cross-linked composition, the cross-linked composition comprising (i) an ethylene polymer, and (ii) a bond having structure (2)

[0006]

[0007] The coating is formed from the following starting materials: an ethylene polymer and 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS) methacrylate. The method includes heating the coating to a reprocessing temperature and forming the coating into a reprocessable ethylene polymer composition at the reprocessing temperature. The method includes forming the reprocessable ethylene polymer composition into a reprocessable preform at the reprocessing temperature. The method includes cooling the reprocessed preform to below the reprocessing temperature and forming a second article composed of a recrosslinked ethylene polymer composition, the recrosslinked ethylene polymer composition consisting of: (i) an ethylene polymer and (ii) a bond having structure (2).

[0008] definition

[0009] All references to the Periodic Table of the Elements herein shall refer to the Periodic Table of the Elements published and copyrighted by CRC Press, Inc. in 2003. Furthermore, any reference to one or more groups shall be to the one or more groups reflected in such Periodic Table of the Elements using the IUPAC system for numbering groups. Unless stated to the contrary, implied by the context, or customary in the art, all parts and percentages are by weight. For purposes of U.S. patent practice, any patent, patent application, or publication referred to herein is incorporated herein by reference in its entirety (or its equivalent U.S. version is so incorporated by reference).

[0010] The numerical range disclosed herein includes all values ​​from the lower limit to the upper limit and including the lower limit and the upper limit. For a range containing clear values ​​(e.g., a range of 1 or 2, or 3 to 5, or 6, or 7), any sub-range between any two clear values ​​is included (e.g., the above range 1 to 7 includes 1 to 2; 2 to 6; 5 to 7; 3 to 7; 5 to 6; etc.).

[0011] Unless stated to the contrary, implicit from the context, or customary in the art, all parts and percentages are by weight and all test methods are current as of the filing date of this disclosure.

[0012] The term "composition" as used herein refers to a mixture of materials which comprise the composition, as well as reaction products and decomposition products formed from the materials of the composition.

[0013] The terms "comprising," "including," "having," and derivatives thereof are not intended to exclude the presence of any additional components, steps, or procedures, whether or not specifically disclosed. For the avoidance of any doubt, all compositions claimed through use of the term "comprising" may include any additional additives, adjuvants, or compounds, whether polymeric or otherwise, unless stated to the contrary. In contrast, the term "consisting essentially of excludes from the scope of any subsequently recited component, step, or procedure, except those that are not essential to operability. The term "consisting of excludes any component, step, or procedure not specifically recited or listed.

[0014] "Ethylene polymers" are polymers containing more than 50 mol% of polymerized ethylene monomers (based on the total amount of polymerizable monomers) and optionally may contain at least one comonomer. Ethylene polymers include ethylene homopolymers and ethylene copolymers (meaning units derived from ethylene and one or more comonomers). The terms "ethylene polymers" and "polyethylene" are used interchangeably. Non-limiting examples of ethylene polymers (polyethylene) include low density polyethylene (LDPE) and linear polyethylene. Non-limiting examples of linear polyethylene include linear low density polyethylene (LLDPE), ultra low density polyethylene (ULDPE), very low density polyethylene (VLDPE), ethylene / α-olefin multi-block copolymers (also known as olefin block copolymers (OBC)), substantially linear or linear plastomers / elastomers, and high density polyethylene (HDPE). Generally speaking, polyethylene can be produced in a gas phase fluidized bed reactor, a liquid phase slurry reactor or a liquid phase solution reactor using a heterogeneous catalyst system (such as a Ziegler-Natta catalyst), a homogeneous catalyst system comprising a Group 4 transition metal and a ligand structure (such as a metallocene, a non-metallocene metal center, a heteroaryl, an isovalent aryloxy ether, a phosphinimine, etc.). Combinations of heterogeneous and / or homogeneous catalysts can also be used in a single reactor or multiple reactor configurations.

[0015] An "ethylene plastomer / elastomer" is a substantially linear or linear ethylene / α-olefin interpolymer containing a homogeneous distribution of short chain branches and comprising units derived from ethylene and from at least one C 3 -C 10 The ethylene plastomers / elastomers have a density of 0.8540 g / cc to 0.917 g / cc. Non-limiting examples of ethylene plastomers / elastomers include AFFINITY TM Polyolefin plastomers and ENGAGE TM Polyolefin elastomer (available from The Dow Chemical Company), EXACT TM Plastomers (available from ExxonMobil Chemical), Tafmer TM α-olefin copolymer (available from Mitsui), Solumer TM Polyolefin Elastomers and Supreme TM Polyolefin plastomers (available from SK Chemicals Co.) and Lucene TM Polyolefin elastomer (available from LG Chem Ltd.).

[0016] "High density polyethylene" (or "HDPE") is a homopolymer of ethylene or ethylene with at least one C4 -C 10 α-olefin comonomer or C 4 -C 8 The HDPE copolymer is an ethylene / α-olefin copolymer having an α-olefin comonomer and a density of 0.940 g / cc, or 0.945 g / cc, or 0.950 g / cc, 0.953 g / cc to 0.955 g / cc, or 0.960 g / cc, or 0.965 g / cc, or 0.970 g / cc, or 0.975 g / cc, or 0.980 g / cc. The HDPE can be a unimodal copolymer or a multimodal copolymer. A "unimodal ethylene copolymer" is an ethylene / α-olefin copolymer having one distinct peak in a gel permeation chromatography (GPC) showing a molecular weight distribution. 4 -C 10 A "multimodal ethylene copolymer" is an ethylene / C-olefin copolymer having at least two distinct peaks in a GPC graph showing molecular weight distribution. 4 -C 10 α-olefin copolymers. Multimodal includes copolymers with two peaks (bimodal) and copolymers with more than two peaks. Non-limiting examples of HDPE include DOW TM High-density polyethylene (HDPE) resin (available from The Dow Chemical Company), ELITE TM Enhanced polyethylene resin (available from The Dow Chemical Company), CONTINUUM TM Bimodal polyethylene resin (available from The Dow Chemical Company), LUPOLEN TM (available from LyondellBasell) and HDPE products from Borealis, Ineos and ExxonMobil.

[0017] "Linear low density polyethylene" (or "LLDPE") is a linear ethylene / α-olefin copolymer containing a homogeneous or heterogeneous distribution of short chain branching, which comprises units derived from ethylene and derived from at least one C 3 -C 10 α-olefins or C 4 -C 8 Units of α-olefin comonomers. LLDPE is characterized by minimal long chain branching (if any) compared to conventional LDPE. LLDPE has a density of 0.910 g / cc to less than 0.940 g / cc. Non-limiting examples of LLDPE include ELITE TM Enhanced polyethylene resin, TUFLIN TM Linear low density polyethylene resin (available from The Dow Chemical Company), DOWLEX TM Polyethylene resin (available from The Dow Chemical Company) and MARLEXTM Polyethylene (available from Chevron Phillips).

[0018] "Low density polyethylene" (or "LDPE") is a homopolymer of ethylene or at least one C 3 -C 10 α-olefins or C 4 -C 8 LDPE is composed of ethylene / α-olefin copolymers of α-olefins and contains long chain branches with broad MWD. ​​LDPE is usually produced by high pressure free radical polymerization (tubular reactor or autoclave with free radical initiator). Non-limiting examples of LDPE include AGILITY TM High performance LDPE and DOW TM LDPE (available from Dow Chemical Company), MarFlex TM (Chevron Phillips Company), LUPOLEN TM (LyondellBasell) and LDPE products from Borealis, INEOS and ExxonMobil, among others.

[0019] As used herein, "olefin polymer" or "polyolefin" is a polymer containing more than 50 mole % polymerized olefin monomer (based on the total amount of polymerizable monomers) and optionally may contain at least one comonomer. Non-limiting examples of olefin polymers include ethylene polymers and propylene polymers.

[0020] "Polymer" is a compound prepared by polymerizing monomers of the same or different types that provide multiple and / or repeating "units" or "monomer units" constituting the polymer in a polymerized form. Therefore, the general term polymer covers the term homopolymer, which is usually used to refer to polymers prepared from only one type of monomer, and the term copolymer, which is usually used to refer to polymers prepared from at least two types of monomers. The general term also covers all forms of copolymers, such as random copolymers, block copolymers, etc. The terms "ethylene / α-olefin polymer" and "propylene / α-olefin polymer" represent copolymers prepared by polymerizing ethylene or propylene and one or more other polymerizable α-olefin monomers, respectively, as described above. It should be noted that although polymers are often referred to as being "made of" one or more specific monomers, "based on" a specific monomer or monomer type, "containing" a specific monomer content, etc., in this context, the term "monomer" should be understood to refer to the polymerized remains of a specific monomer, rather than an unpolymerized species. In general, polymers herein refer to "units" based on the polymerized form of the corresponding monomer.

[0021] Test Method

[0022] Compression set Compression set (or "Cset") was measured according to ASTM D395 Method B and Type 1 sample dimensions using one specimen per sample with 25% strain at 70°C for 22 hours (h) and 25% strain at 100°C for 22 hours.

[0023] density Measured according to ASTM D792, with results reported in g / cc at 25°C.

[0024] Rheological properties analysis Use rubber processing analyzer (RPA). According to ASTM D6204, the rheological properties of the composition are measured under the following test conditions and exceptions using a rotorless oscillating shear rheometer, i.e., Alpha Technologies RPA 2000 instrument. The sample is placed between two polyester films for analysis. The rheological properties are monitored during the initial timing test, and 60 minutes are monitored at 160°C, 1.0rad / s, and 7% strain. The elastic torque S' at the end of the 60-minute crosslinking step is recorded. After 60 minutes at 160°C, a frequency sweep of 0.1rad / s to 300rad / s is immediately performed on the same sample at 160°C, 7% strain, followed by a frequency sweep of 0.1rad / s to 300rad / s at 190°C, 7% strain, and then a frequency sweep of 0.1rad / s to 300rad / s at 230°C, 7% strain. The dynamic complex viscosity n* and tanδ of each frequency sweep are recorded. In ASTM D6204, a frequency sweep is performed on unvulcanized rubber before the curing step. In this case, a frequency sweep was performed after an initial cross-linking step at 160 °C to evaluate the reversibility of the cross-linking.

[0025] Dynamic Mechanical Analysis (DMA) DMA experiments were performed using a TA Instruments RSA-G2 solid analyzer to measure the storage modulus (G'), loss modulus (G"), and damping ratio (tan δ) of the networks as a function of temperature and recovery under a nitrogen atmosphere. The DMA was operated in tension mode with a frequency of 1 Hz and an oscillating strain of 0.03%. Data were collected from room temperature to 160 °C at a heating rate of 3 °C / min.

[0026] Melt Index (MI or I 2 ) (For ethylene polymers) is measured according to ASTM D 1238, Condition 190°C / 2.16 kg, where the results are reported in grams per 10 minutes (g / 10 min).

[0027] Tensile measurement at 80°C. According to the ASTM D1708 standard, tensile measurements are performed on an INSTRON device at a tensile speed of 1 inch / minute. Tensile test bars are prepared by die cutting from compression molded sheets with a thickness of 1.5 mm. The test is carried out in an environmental chamber, where the temperature is balanced at 80°C for 30 minutes before testing. Here, the tensile strength, i.e. the maximum stress applied before the sample breaks, is recorded to reflect whether the material has cross-linked properties. These parameters are averaged over 3 repeated tensile measurements. The cross-linked portion generally has a significantly higher tensile strength at break than the non-cross-linked portion. DETAILED DESCRIPTION

[0028] The present disclosure relates to an article. The article includes an extruded profile. The extruded profile is composed of a cross-linked polymer composition formed from starting materials including: (i) an ethylene polymer and (ii) 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate).

[0029] A. Extrusion Profiles

[0030] The present disclosure relates to a kind of article, and this article comprises or is extruded profile.As used herein, " extruded profile " (or " profile ") is made of polymer composition and has the three-dimensional shaped object of length, width and height, and this shaped object has constant cross-sectional shape along its length.This cross-sectional shape is constant (or is uniform) along the whole length of shaped object or along substantially whole length.Extruded profile is formed by forcing molten polymer composition to pass through die outlet and cooling molten polymer when leaving from die outlet.Non-limiting examples of (constant) cross-sectional shape of extruded profile include circle, ellipse, polygon, ring, triangle, square and rectangle.Non-limiting examples of extruded profile include film, fiber, rod, rod, pipe, pipeline, sheet, rubber tube, extruded automotive rubber profile and sealing strip.

[0031] B. Ethylene polymers

[0032] The article including (or being) an extruded profile is formed from a crosslinkable polymer composition (interchangeably referred to as a "starting material") comprising an ethylene polymer. The ethylene polymer may be an ethylene homopolymer, an ethylene / C 3 -C 10 α-olefin copolymer or ethylene C 4 -C 8Alpha-olefin copolymers. The melt index (MI) of the ethylene polymer is 0.1 g / 10min to 100 g / 10min, or 1 g / 10min to 100 g / 10min, or 1 g / 10min to 50 g / 10min, or 1 g / 10min to 25 g / 10min, or 1 g / 10min to 10 g / 10min, or 1 g / 10min to 5 g / 10min. Non-limiting examples of suitable ethylene polymers include ethylene plastomers / elastomers, high density polyethylene (HDPE), linear low density polyethylene (LLDPE), low density polyethylene (LDPE), ethylene / alpha-olefin multi-block copolymers, and combinations thereof.

[0033] In one embodiment, the ethylene-based polymer is an ethylene plastomer / elastomer.

[0034] In one embodiment, the ethylene-based polymer is HDPE.

[0035] In one embodiment, the ethylene-based polymer is LLDPE.

[0036] In one embodiment, the ethylene polymer is an ethylene / α-olefin multi-block copolymer. The term "ethylene / α-olefin multi-block copolymer" refers to a copolymer of ethylene and a copolymerizable C 4 -C 8 α-olefin comonomer (and optional additives) composed of ethylene / C 4 -C 8 α-olefin multi-block copolymers, polymers characterized by multiple blocks or segments of two polymerized monomer units that differ in chemical or physical properties, the blocks being linked (or covalently bonded) in a linear manner, i.e., polymers comprising chemically distinguishable units linked end-to-end with respect to polymerized olefinic functionality. Ethylene / α-olefin multi-block copolymers include block copolymers having two blocks (diblocks) and more than two blocks (multiblocks). C 3 –C 8 The α-olefin is selected from propylene, butene, hexene and octene. The ethylene / α-olefin multi-block copolymer is free of or contains no styrene (i.e., is styrene-free), and / or vinyl aromatic monomers, and / or conjugated dienes. When referring to the amount of "ethylene" or "comonomer" in the copolymer, it is understood that this refers to polymerized units thereof. In some embodiments, the ethylene / α-olefin multi-block copolymer can be represented by the following formula: (AB) n; wherein n is at least 1, preferably an integer greater than 1, such as 2, 3, 4, 5, 10, 15, 20, 30, 40, 50, 60, 70, 80, 90, 100 or more, "A" represents a hard block or segment and "B" represents a soft block or segment. Preferably, A and B are connected or covalently bonded in a substantially linear manner, or in a linear manner, relative to a substantially branched or substantially star-shaped manner. In other embodiments, the A blocks and B blocks are randomly distributed along the polymer chain. In other words, the block copolymer generally does not have the following structure: AAA-AA-BBB-BB. In one embodiment, the ethylene / α-olefin multi-block copolymer does not have a third type of block, which comprises one or more different comonomers. In another embodiment, block A and block B each have monomers or comonomers that are substantially randomly distributed within the block. In other words, neither block A nor block B comprises two or more subsegments (or subblocks) of different compositions, such as an end segment having a substantially different composition than the remainder of the block.

[0037] In one embodiment, ethylene constitutes the majority of the mole fraction of the entire ethylene / α-olefin multi-block copolymer, i.e., ethylene constitutes at least 50% by weight of the entire ethylene / α-olefin multi-block copolymer. More preferably, ethylene constitutes at least 60% by weight, at least 70% by weight, or at least 80% by weight, and the substantial remainder of the entire ethylene / α-olefin multi-block copolymer comprises C 3 -C 8 α-olefin comonomer. In one embodiment, the ethylene / α-olefin multi-block copolymer contains 50 wt% to 90 wt% ethylene, or 60 wt% to 85 wt% ethylene, or 65 wt% to 80 wt% ethylene. For various ethylene / octene multi-block copolymers, the composition comprises an ethylene content greater than 80 wt% of the entire ethylene / octene multi-block copolymer and an octene content of 10 wt% to 15 wt%, or 15 wt% to 20 wt% of the entire multi-block copolymer.

[0038] Ethylene / alpha-olefin multi-block copolymers include various amounts of "hard" segments and "soft" segments. "Hard" segments are blocks of polymerized units, wherein based on the weight of the polymer, ethylene is present in an amount greater than 90 wt %, or 95 wt %, or greater than 95 wt %, or greater than 98 wt %, up to 100 wt %. In other words, by the weight of the polymer, the comonomer content (except the monomer content of ethylene) in the hard segments is less than 10 wt %, or 5 wt %, or less than 5 wt %, or less than 2 wt %, and can be as low as zero. In some embodiments, the hard segments include all or substantially all units derived from ethylene. "Soft" segments are blocks of polymerized units, in which, by the weight of the polymer, the comonomer content (the content of monomers other than ethylene) is greater than 5 wt %, or greater than 8 wt %, greater than 10 wt %, or greater than 15 wt %. In one embodiment, the comonomer content in the soft segments is greater than 20 wt%, greater than 25 wt%, greater than 30 wt%, greater than 35 wt%, greater than 40 wt%, greater than 45 wt%, greater than 50 wt%, or greater than 60 wt% and can be as high as 100 wt%.

[0039] The soft segment can be present in ethylene / alpha-olefin multi-block copolymers from 1% to 99% by weight of the total weight of the ethylene / alpha-olefin multi-block copolymer, or from 5% to 95% by weight, 10% to 90% by weight, 15% to 85% by weight, 20% to 80% by weight, 25% to 75% by weight, 30% to 70% by weight, 35% to 65% by weight, 40% to 60% by weight, or 45% to 55% by weight of the total weight of the ethylene / alpha-olefin multi-block copolymer. On the contrary, the hard segment can be present in a similar range. The soft segment weight percentage and the hard segment weight percentage can be calculated based on the data obtained from DSC or NMR. Such methods and calculations are disclosed in, for example, USP 7,608,668, entitled "Ethylene / α-Olefin Block Inter-Polymers", filed on March 15, 2006 in the name of Colin L.P. Shan, Lonnie Hazlitt et al. and assigned to Dow Global Technologies Inc., the disclosure of which is incorporated herein by reference in its entirety. Specifically, the hard segment weight percentage and the soft segment weight percentage and the comonomer content can be determined as described in columns 57 to 63 of USP 7,608,668.

[0040] The ethylene / α-olefin multi-block copolymer comprises two or more chemically distinct regions or segments (referred to as "blocks") that are linked (or covalently bonded) in a linear manner, i.e., they contain chemically distinguishable units that are linked end-to-end with respect to the polymerized olefinic functionality, rather than in a pendant or grafted manner. In one embodiment, the blocks differ in the amount or type of comonomer incorporated, density, amount of crystallinity, crystallite size attributable to polymers of such compositions, type or degree of stereoisomerism (isotactic or syndiotactic), regioregularity or regioirregularity, amount of branching (including long chain branching or hyperbranching), uniformity, or any other chemical or physical characteristic. Compared to prior art block interpolymers, including those produced by sequential monomer addition, stereolabile catalysts, or anionic polymerization techniques, the inventive ethylene / α-olefin multi-block copolymers are characterized by a unique distribution of polymer polydispersity (PDI or Mw / Mn or MWD), polydisperse block length distribution, and / or polydisperse block number distribution, which, in one embodiment, is due to the effect of one or more shuttling agents in combination with various catalysts used in their preparation.

[0041] In one embodiment, the ethylene / α-olefin multi-block copolymer is produced in a continuous process and has a polydispersity index (Mw / Mn) of 1.7 to 3.5, or 1.8 to 3, or 1.8 to 2.5, or 1.8 to 2.2. When prepared in a batch or semi-batch process, the ethylene / α-olefin multi-block copolymer has a Mw / Mn of 1.0 to 3.5, or 1.3 to 3, or 1.4 to 2.5, or 1.4 to 2.

[0042] In addition, the ethylene / α-olefin multi-block copolymer has a PDI (or Mw / Mn) that fits the Schultz-Flory distribution rather than the Poisson distribution. The ethylene / α-olefin multi-block copolymer of the present invention has both a polydisperse block distribution and a polydisperse distribution of block sizes. This results in the formation of a polymer product with improved and distinguishable physical properties. The theoretical benefits of a polydisperse block distribution have been previously described in Potemkin, Physical Review E( Physical Review ) (1998) 57(6), pp. 6902-6912 and Dobrynin, Journal of Chemical Physics ( J.Chem.Phvs.)》 The theoretical benefits of polydisperse block distributions are modeled and discussed in (1997) 107(21), pp. 9234-9238.

[0043] In one embodiment, the ethylene / α-olefin multi-block copolymers of the present invention have a most probable distribution of block lengths.

[0044] In another embodiment, the ethylene / α-olefin multi-block copolymers of the present disclosure, especially those copolymers made in a continuous solution polymerization reactor, have the most probable distribution of block lengths. In one embodiment of the present disclosure, the ethylene / α-olefin multi-block copolymers are defined as having:

[0045] (A) an Mw / Mn of from about 1.7 to about 3.5, at least one melting point Tm in degrees Celsius, and a density d in grams per cubic centimeter, wherein the numerical values ​​of Tm and d correspond to the following relationship:

[0046] Tm>-2002.9+4538.5(d)-2422.2(d) 2 , and / or

[0047] (B) an Mw / Mn of from about 1.7 to about 3.5, and is characterized by a heat of fusion, DH, in J / g, and a differential, DT, in degrees Celsius, defined as the temperature difference between the tallest DSC peak and the tallest Crystallization Analysis Separation ("CRYSTAF") peak, wherein the numerical values ​​of DT and DH have the following relationship:

[0048] For DH greater than zero and up to 130 J / g, DT>-0.1299DH+62.81

[0049] For DH greater than 130 J / g, DT ≥ 48 °C

[0050] wherein at least 5% of the cumulative polymer is used to determine the CRYSTAF peak, and if less than 5% of the polymer has an identifiable CRYSTAF peak, then the CRYSTAF temperature is 30°C; and / or

[0051] (C) an elastic recovery Re in percent measured at 300% stress and 1 cycle with a compression molded ethylene / α-olefin interpolymer film, and a density d in grams per cubic centimeter, wherein when the ethylene / α-olefin interpolymer is substantially free of a crosslinked phase, the values ​​of Re and d satisfy the following relationship:

[0052] Re>1481–1629(d); and / or

[0053] (D) having a molecular fraction eluting between 40°C and 130°C when fractionated using TREF, characterized in that said fraction has a molar comonomer content at least 5% higher than an equivalent comparable random ethylene interpolymer fraction eluting between the same temperatures, wherein said comparable random ethylene interpolymer has the same comonomers and has a melt index, density, and molar comonomer content (based on the whole polymer) within 10% of that of an interpolymer of ethylene / α-olefin; and / or

[0054] (E) has a storage modulus G'(25°C) at 25°C and a storage modulus G'(100°C) at 100°C, wherein a ratio of G'(25°C) to G'(100°C) is in a range of 1:1 to 9:1.

[0055] The ethylene / α-olefin multi-block copolymer may also have:

[0056] (F) a molecular fraction eluting between 40°C and 130°C when fractionated using TREF, characterized in that the block index of the fraction is at least 0.5 and at most 1, and the molecular weight distribution Mw / Mn is greater than 1.3; and / or

[0057] (G) The average block index is greater than zero and at most 1.0, and the molecular weight distribution Mw / Mn is greater than 1.3.

[0058] It should be understood that the ethylene / α-olefin multi-block copolymer may have one, some, all or any combination of properties (A)-(G). The block index may be determined as described in detail in USP 7,608,668, which is incorporated herein by reference for the purpose. Analytical methods for determining properties (A) to (G) are disclosed, for example, in USP 7,608,668, column 31, line 26 to column 35, line 44, which is incorporated herein by reference for the purpose.

[0059] In one embodiment, the ethylene / α-olefin multi-block copolymer has hard segments and soft segments, is free of styrene, and is composed only of (i) ethylene and (ii) C 4 -C 8 α-olefins or C 8 α-olefins (and optional additives), and is defined as having a Mw / Mn of 1.7 to 3.5, at least one melting point Tm in degrees Celsius and a density d in grams per cubic centimeter, wherein the numerical values ​​of Tm and d correspond to the following relationship:

[0060] Tm>-2002.9+4538.5(d)-2422.2(d) 2 ,

[0061] wherein the density d is 0.850 g / cc, or 0.860 g / cc, or 0.870 g / cc to 0.875 g / cc, or 0.877 g / cc, or 0.880 g / cc, or 0.890 g / cc; and the melting point Tm is 110°C, or 115°C, or 120°C to 125°C, or 130°C, or 135°C.

[0062] In one embodiment, the ethylene / α-olefin multi-block copolymer is an ethylene / 1-octene multi-block copolymer (consisting only of ethylene and octene comonomers) and has one, some or all of the following characteristics:

[0063] (i) an Mw / Mn of from 1.7, or 1.8 to 2.2, or 2.5, or 3.5; and / or

[0064] (ii) a density of 0.860 g / cc, or 0.865 g / cc to 0.870 g / cc, or 0.877 g / cc, or 0.880 g / cc; and / or

[0065] (iii) a melting point Tm of 115°C, or 118°C, or 119°C, or 120°C to 120°C, or 123°C, or 125°C; and / or

[0066] (iv) a melt index (MI) of 0.1 g / 10 min, or 0.5 g / 10 min to 1.0 g / 10 min, or 2.0 g / 10 min, or 5 g / 10 min, or 10 g / 10 min; and / or

[0067] (v) 50 to 85 weight percent soft segments and 40 to 15 weight percent hard segments (based on the total weight of the ethylene / octene multi-block copolymer); and / or

[0068] (vi) 10 mol%, or 13 mol%, or 14 mol%, or 15 mol% to 16 mol%, or 17 mol%, or 18 mol%, or 19 mol%, or 20 mol% octene in the soft segment; and / or

[0069] (vii) 0.5 mol%, or 1.0 mol%, or 2.0 mol%, or 3.0 mol% to 4.0 mol%, or 5 mol%, or 6 mol%, or 7 mol%, or 9 mol% of octene in the hard segments; and / or

[0070] (viii) 300% min at 21°C as measured according to ASTM D 1708 ·1 50%, or 60% to 70%, or 80%, or 90% elastic recovery (Re) at deformation rate; and / or

[0071] (ix) Polydispersity distribution of blocks and polydispersity distribution of block sizes (hereinafter referred to as multi-block copolymer properties (i) to (ix)).

[0072] In one embodiment, the ethylene / α-olefin multi-block copolymer is an ethylene / octene multi-block copolymer. The ethylene / octene multi-block copolymer is marketed under the trade name INFUSE TMSold and available from The Dow Chemical Company, Midland, Michigan, USA.

[0073] Ethylene / α-olefin multi-block copolymers can be produced via a chain shuttling process as described in USP 7,858,706, which is incorporated herein by reference. Specifically, suitable chain shuttling agents and related information are listed in column 16, line 39 to column 19, line 44. Suitable catalysts are described in column 19, line 45 to column 46, line 19 and suitable co-catalysts are described in column 46, line 20 to column 51, line 28. The process is described throughout the literature, but especially in column 51, line 29 to column 54, line 56. The process is also described, for example, in the following: USP 7,608,668; USP 7,893,166; and USP 7,947,793.

[0074] C. Free Radical Initiator

[0075] The crosslinkable polymer composition formed into the extruded profile includes a free radical initiator. In one embodiment, the free radical initiator is an organic peroxide. Non-limiting examples of suitable organic peroxides include bis(1,1-dimethylethyl)peroxide; bis(1,1-dimethylpropyl)peroxide; 2,5-dimethyl-2,5-bis(1,1-dimethylethylperoxy)hexane; 2,5-dimethyl-2,5-bis(1,1-dimethylethylperoxy)hexyne; 4,4-bis(1,1-dimethylethylperoxy)pentanoic acid; butyl ester; 1,1-bis(1,1-dimethylethylperoxy)-3,3,5-trimethylcyclohexane; benzoyl peroxide; tert-butyl peroxybenzoate; di-tert-amyl peroxide ( "DTAP"); bis(α-tert-butylperoxyisopropyl)benzene ("BIPB"); isopropylcumyl tert-butyl peroxide; tert-butylcumyl peroxide; di-tert-butyl peroxide; 2,5-bis(tert-butylperoxy)-2,5-dimethylhexane; 2,5-bis(tert-butylperoxy)-2,5-dimethylhexyne-3,1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane; isopropylcumylcumyl peroxide; butyl 4,4-di(tert-butylperoxy)valerate; di(isopropylcumyl) peroxide; diisopropylbenzene peroxide, and combinations thereof.

[0076] In one embodiment, the free radical initiator is dicumyl peroxide.

[0077] D.BiTEMPS Methacrylate

[0078] The crosslinkable polymer composition from which the extruded profile is formed comprises 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide, interchangeably referred to as "BiTEMPS methacrylate" or "BiTEMPS" or "BiT." BiTEMPS methacrylate disulfide has the following structure 1.

[0079] Structure 1

[0080]

[0081] In one embodiment, the crosslinkable polymer composition comprises:

[0082] 70 wt % to 98.5 wt %, or 77 wt % to 98.5 wt % of an ethylene polymer;

[0083] 0.1 wt % to 10 wt %, or 0.1 wt % to 5 wt %, 0.1 wt % to 3.0 wt %, or 0.1 wt % to 1.5 wt %, or 0.5 wt % to 1.5 wt % of a free radical initiator, which is an organic peroxide (e.g., dicumyl peroxide); and

[0084] 1 wt % to 20 wt %, or 1 wt % to 15 wt %, or 2 wt % to 20 wt %, or 2 wt % to 10 wt % BiTEMPS methacrylate disulfide. It is understood that the aggregate of the vinyl polymer, free radical initiator, and BiTEMPS methacrylate disulfide (and optional additives) totals 100 wt % of the crosslinkable polymer composition.

[0085] The cross-linked composition for extruded profiles is formed from a cross-linkable polymer composition. The cross-linkable polymer composition is melt blended at a temperature of 100°C to 250°C, or 120°C to 210°C, or 140°C to 210°C, or 140°C to 190°C to trigger a cross-linking reaction and form a cross-linked composition. In one embodiment, the cross-linked composition comprises an ethylene polymer and 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate). The cross-linked composition contains a disulfide bond formed by BiTEMPS methacrylate through a cross-linking reaction, and the disulfide bond has the following structure 2.

[0086] Structure 2

[0087]

[0088] The term (and structure) "P" in Structure 2 above refers to the chains of polymerized ethylene (and optional comonomers) of the ethylene polymer. The ethylene polymer of the crosslinked composition can be any ethylene polymer having a MI of 0.1 g / 10 min to 100 g / 10 min as previously disclosed herein. Non-limiting examples of suitable ethylene polymers include ethylene plastomers / elastomers, high density polyethylene (HDPE), linear low density polyethylene (LLDPE), low density polyethylene (LDPE), ethylene / α-olefin multi-block copolymers, and combinations thereof.

[0089] In one embodiment, the olefinic polymer is a native olefinic polymer. As used herein, a "native olefinic polymer" is an olefinic polymer that has not been subjected to a crosslinking reaction. In other words, the term "native olefinic polymer" refers to the olefinic polymer that was present in the crosslinked composition before the olefinic polymer was crosslinked with the BiTEMPS methacrylate. The native olefinic polymer is the olefinic polymer prior to crosslinking, and the crosslinked composition comprises the same olefinic polymer that is native but now crosslinked with the BiTEMPS methacrylate. In this way, the native olefinic polymer is used as a benchmark for evaluating the performance of the crosslinked composition. The crosslinked composition has

[0090] (i) a storage modulus value G' at 140°C that is greater than the storage modulus value E' of the native ethylene polymer at 140°C;

[0091] (ii) a tan δ value at 60°C that is less than the tan δ value of the virgin ethylene polymer at 60°C;

[0092] as well as

[0093] (iii) a tan δ value at 140°C that is less than the tan δ value of the virgin ethylene polymer at 140°C,

[0094] And formed into an extruded profile as disclosed above.

[0095] In one embodiment, the crosslinked composition comprises 80 wt% to 99.9 wt% or 80 wt% to 97 wt% of an ethylene polymer and a bond having structure (2) (formed by 2 wt% to 20 wt% of BiTEMPS methacrylate), the aggregate of the ethylene polymer and the bond having structure (2) (formed by BiTEMPS methacrylate) (and optional additives) totaling 100 wt% of the crosslinked composition. The crosslinked composition of the extruded profile has

[0096] (i) a storage modulus value G' greater than 1 MPa at 60°C;

[0097] (ii) a storage modulus value G' at 140°C greater than 0.1 MPa;

[0098] (iii) a tan delta value of less than 0.17 at 60°C; and

[0099] (iv) a tan δ value of less than 0.62 at 140°C.

[0100] E. Blend Components

[0101] In one embodiment, the crosslinkable polymer composition and / or the crosslinked composition comprises a blend component. Non-limiting examples of suitable blend components include ethylene vinyl acetate (EVA), polyolefins (e.g., polyethylene other than ethylene polymers crosslinked with BiTEMPS methacrylate and polypropylene), polymers (e.g., polystyrene, ABS, SBS, etc.), and combinations thereof. Non-limiting examples of suitable polyolefins include polyethylene; polypropylene; polybutene (e.g., polybutene-1); polypentene-1; polyhexene-1; polyoctene-1; polydecene-1; poly-3-methylbutene-1; poly-4-methylpentene-1; polyisoprene; polybutadiene; poly-1,5-hexadiene; interpolymers derived from olefins; interpolymers derived from olefins and other polymers such as polyvinyl chloride, polystyrene, polyurethane, etc.; and mixtures thereof.

[0102] In one embodiment, the polyolefin is a homopolymer such as polyethylene, polypropylene, polybutene, polypentene-1, poly-3-methylbutene-1, poly-4-methylpentene-1, polyisoprene, polybutadiene, poly-1,5-hexadiene, polyhexene-1, polyoctene-1, and polydecene-1.

[0103] Non-limiting examples of polyethylenes suitable as blend components (other than ethylene polymers crosslinked with BITEMPS methacrylate) include ultra low density polyethylene (ULDPE), linear low density polyethylene (LLDPE), low density polyethylene (LDPE), medium density polyethylene (MDPE), high density polyethylene (HDPE), high molecular weight high density polyethylene (HMW-HDPE), ultra high molecular weight polyethylene (UHMW-PE), and combinations thereof. Non-limiting examples of polypropylenes include low density polypropylene (LDPP), high density polypropylene (HDPP), high melt strength polypropylene (HMS-PP), and combinations thereof. In one embodiment, the blend component is high melt strength polypropylene (HMS-PP), low density polyethylene (LDPE), or combinations thereof.

[0104] F. Additives

[0105] The crosslinkable polymer composition and / or the crosslinked composition may contain one or more optional additives. Non-limiting examples of suitable additives include grafting initiators, crosslinking catalysts, blowing agents, blowing agent activators (e.g., zinc oxide, zinc stearate, etc.), auxiliary agents (e.g., triallyl cyanurate), plasticizers, processing oils, processing aids, carbon black, colorants or pigments, stability control agents, nucleating agents, fillers, antioxidants, acid scavengers, ultraviolet (UV) stabilizers, flame retardants, lubricants, processing aids, extrusion aids, and combinations thereof. When present, the total amount of the additive may be greater than 0% to 80%, or 0.001% to 70%, or 0.01% to 60%, or 0.1% to 50%, or 0.1% to 40%, or 0.1% to 20%, or 0.1% to 10%, or 0.1% to 5% of the total weight of the composition.

[0106] BiTEMPS methacrylate is a "dynamic crosslinker". The dynamic crosslinker BiTEMPS methacrylate enables the formation of a crosslinked network with ethylene polymers through disulfide bonds between the chains of the ethylene polymers (in the presence of a free radical initiator), thereby forming a crosslinked ethylene polymer composition. The crosslinking is dynamic because the disulfide bonds can be broken when the crosslinked ethylene polymer composition is subjected to a "reprocessing temperature", thereby allowing chain movement and exchange, which is a temperature of 160°C to 230°C, or 160°C to 200°C. At the reprocessing temperature, the disulfide bonds in the crosslinked ethylene polymer composition are broken to form a reprocessable ethylene polymer composition. The reprocessable ethylene composition is cooled to below the reprocessing temperature to form a re-crosslinked ethylene polymer composition.

[0107] The dynamic crosslinker BiTEMPS methacrylate enables cyclic "reprocessing" to make new polymer articles. When the crosslinked ethylene polymer composition is heated to the reprocessing temperature, the disulfide bonds are broken or otherwise cleaved, allowing the previously crosslinked ethylene polymer composition to flow at the reprocessing temperature, thereby forming a "reprocessable ethylene polymer composition". Heating to the reprocessing temperature enables chain scission and polymer chain flow, thereby allowing the ethylene composition to be easily reshaped. At the reprocessing temperature, the reprocessable ethylene polymer composition is no longer crosslinked, but is flowable, allowing the now flowable, reprocessable ethylene composition (with BiTEMPS methacrylate) to be shaped and / or manufactured into a new preform or article. When cooled to below the "reprocessing temperature", the disulfide bonds are formed again, the network is reestablished, and the re-crosslinked ethylene composition is formed in a new article configuration, returning to high viscosity (no flow at room temperature) and resistance to mechanical deformation indicating a crosslinked network. When the newly formed article of the reprocessable ethylene polymer composition is cooled to below the reprocessing temperature, the disulfide bonds in the reprocessable ethylene polymer composition are reestablished and the ethylene polymer (with BiTEMPS methacrylate) becomes a recrosslinked ethylene polymer composition in the shape of the newly manufactured article. Below the reprocessing temperature, the network disulfide bonds are stable and the recrosslinked ethylene polymer composition exhibits high viscosity and resistance to mechanical deformation indicative of the crosslinked network. This cycle of crosslinking / reprocessing / recrosslinking and manufacturing into new articles can be repeated.

[0108] Without being bound by a particular theory, the number of "reprocessing" cycles possible for the crosslinked ethylene compositions of the present invention can be determined by calculating the ratio of the melt viscosities of the crosslinked ethylene polymer composition before and after the reprocessing cycle (before competing thermal and oxidative permanent crosslinking occurs and prevents further reprocessing). For reprocessable, crosslinked ethylene polymer compositions, the ratio of the viscosity after reprocessing to the viscosity before reprocessing is from 0.5 to 5, or from 0.7 to 3, or from 0.9 to 2, or from 0.95 to 1.2.

[0109] Other metrics used to monitor the number of "reprocessing" cycles possible for the BiTEMPS methacrylate dynamic crosslinker before competing oxidative permanent crosslinking occurs include visual observation. The mechanically deformed formed film is heated to the reprocessing temperature and visually inspected to determine if the mechanically deformed film has healed to form a stable film.

[0110] G. Methods

[0111] The present disclosure provides a method. In one embodiment, the method includes heating a first article to a reprocessing temperature. The first article is composed of an extruded profile, or an extruded profile. The extruded profile is composed of a cross-linked composition comprising an ethylene polymer and a bond having structure (2) (formed by 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate)). The method includes forming the first article into a reprocessable ethylene polymer composition at a reprocessing temperature. The method includes forming the reprocessable ethylene polymer composition into a reprocessed preform at a reprocessing temperature. The method includes cooling the reprocessed preform to below the reprocessing temperature and forming a second article composed of a recrosslinked ethylene polymer composition, the recrosslinked ethylene polymer composition being composed of: (i) an ethylene polymer and (ii) BiTEMPS methacrylate.

[0112] The second article may be the same as or different from the first article.

[0113] In one embodiment, the forming step is a procedure selected from the group consisting of injection molding, extrusion, extrusion molding, thermoforming, blow molding, overmolding, insert molding, blow molding, casting, tentering, compression molding, and combinations thereof.

[0114] Non-limiting examples of suitable second articles for the cross-linked / re-cross-linked ethylene polymer (with BiTEMPS methacrylate) compositions of the present invention include three-dimensional loop materials; extruded profiles, elastic films; elastic fibers; soft-touch items such as toothbrush handles and appliance handles; pads and profiles; adhesives (including hot melt adhesives and pressure sensitive adhesives); footwear (including soles and shoe insoles); automotive interior parts and profiles; foam articles (both open-cell and closed-cell foams); impact modifiers for other thermoplastic polymers such as high-density polyethylene, isotactic polypropylene or other olefin polymers; coated fabrics; hoses; pipes; weather strips; lid linings; flooring; and combinations thereof.

[0115] Applicants have discovered cross-linked extruded profiles that can undergo reversible cross-linking at reprocessing temperatures. This is achieved by forming an extruded profile from a cross-linkable polymer composition of an ethylene polymer, a peroxide and BITEMPS methacrylate. The composition of the present invention forms an article consisting of a cross-linked composition, or an extruded profile consisting of a cross-linked composition, wherein the cross-linked composition is cross-linked at the coating use temperature, but can be melt-reprocessed at typical extruded profile processing temperatures (about 160°C-250°C). Therefore, the solution of the present invention provides extruded profiles with benefits in terms of heat resistance and durability, while maintaining (re)processability at typical extrusion temperatures.

[0116] By way of example and not limitation, some embodiments of the present disclosure will now be described in detail in the following examples.

[0117] 1. Materials

[0118] The materials used in the comparative samples (CS) and the inventive examples (IE) are provided in Table 1 below.

[0119] Table 1 - Materials

[0120]

[0121] 2. Synthesis of BITEMPS Methacrylate

[0122] To synthesize BiTEMPS methacrylate, 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (8.78 g, 39.0 mmol, provided by TCI America) was first dissolved in anhydrous petroleum ether (about 90 mL, provided by Sigma-Aldrich, dried over molecular sieves for 48 hours before use) and cooled to -70 °C in a dry ice / acetone bath. Afterwards, sulfur monochloride (1.30 g, 9.7 mmol, provided by Sigma-Aldrich) was dissolved in anhydrous petroleum ether (about 1.25 mL) and added dropwise to the reaction vessel over a 30-minute period. The solution was stirred at -70 °C for another 30 minutes and at room temperature for 15 minutes. Next, BiTEMPS methacrylate was precipitated by pouring the reaction solution into a large amount of distilled water and stirring at room temperature overnight. The precipitate was collected, vacuum filtered, and vacuum dried at 60 °C for 48 hours to obtain BiTEMPS methacrylate as shown in the following structure 1.

[0123] Structure 1

[0124]

[0125] 3. Recipe

[0126] (i) benchmark polyethylene (8842, 9000, 8100), (ii) polyethylene and DCP, and (iii) polyethylene, DCP, and BiTEMPS methacrylate (in the amounts shown in Table 2 below) were combined and mixed in batches at 100°C to form a crosslinkable polymer composition. The crosslinkable polymer composition was heated on an RPA at 160°C for 60 minutes to initiate the crosslinking reaction. The properties of the crosslinked composition are provided in Table 2 below.

[0127] Table 2: Formulation and properties

[0128]

[0129] 4. Cross-linking

[0130] 4" x 3" x 1.5 mm plaques or 1 inch diameter and 0.5 inch thick buttons of the crosslinked composition were prepared in a compression molding machine at 180°C at 30,000 lbf for 15 minutes. The plaques and buttons were then conditioned at room temperature for one day. Tensile testing at 80°C, compression set at 70°C, and compression set at 100°C were evaluated as reported in Table 2.

[0131] Table 3: Summary of materials identified as cross-linked extrusion parts and considered extrudable based on RPA screening of the compounds. Features .

[0132]

[0133] In Table 3, the RPA results are summarized, which indicate whether the material is cross-linked based on the RPA S' value, and whether the cross-linked composition is reprocessable based on the VRR (i.e., viscosity ratio, VRR = RPA n*(0.1) at 160°C / RPA n*(0.1) at 230°C). High RPA S' values ​​indicate that the composition can reach a cross-linked state during the initial curing step. It was also found that the high S' values ​​observed in Table 2 are consistent with the measured physical properties of the cross-linked materials, which include high tensile strength at 80°C and relatively low Cset at 70°C and 100°C compared to non-cross-linked elastomers.

[0134] A high VRR (greater than 5) is required to reprocess the crosslinked material, or to be reprocessable, during extrusion. This is because the viscosity of irreversibly crosslinked materials (compositions with DCP but no BiTEMPS) at processing temperatures such as 230°C generally undergoes a sufficiently low viscosity drop to become extrudable. However, due to the cleavage of the disulfide bonds, each of the inventive examples IE1-IE4 shows a significant drop in viscosity at 230°C - at least a 5-fold drop (i.e., VRR>5), and thus IE1-IE4 are extrudable and reprocessable.

[0135] Table 4 Extrusion of the present invention

[0136]

[0137] For extrusion studies, the crosslinked plaques were cut into small pieces using scissors. 20 grams of each crosslinked composition was fed into a micro-compounder (DSM EXPLORE Micro-compounder MC40) operated between 200°C and 230°C, starting at 25 rpm and increasing to 50 rpm (if possible). The extrusion conditions and observations are shown in Table 4.

[0138] In Table 4, the extrudability of IE2 and IE4 is demonstrated, where each of the inventive examples can be extruded at temperatures between 200°C-230°C after crosslinking (i.e., after curing IE2 and IE4 at 180°C for 15 minutes). Specifically, for extrusion at 230°C, the extruder can be operated at up to 50 RPM and relatively low torque, which is comparable to the ENGAGE 8100 control non-crosslinked resin extruded at 200°C.

[0139] It is particularly intended that the present disclosure is not limited to the embodiments and descriptions contained herein, but includes modifications of those embodiments including parts of the embodiments and combinations of elements of different embodiments as appear within the scope of the following claims.

Claims

1. A product comprising: An extruded profile composed of a crosslinked composition formed from a starting material comprising: Ethylene polymers; and 2,2,6,6-Tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate).

2. The article of claim 1, wherein the crosslinked composition comprises a bond of structure 2 3. The article according to any one of claims 1 to 2, wherein the cross-linking composition comprises: 80 to 99 weight percent of an ethylene-based polymer having a melt index of 0.1 to 100 g / 10 min; and 20 wt % to 1 wt % of said BiTEMPS methacrylate.

4. The article according to any one of claims 1 to 3, wherein the ethylene-based polymer is selected from the group consisting of ethylene plastomers / elastomers, high density polyethylene (HDPE), linear low density polyethylene (LLDPE), low density polyethylene (LDPE), ethylene / α-olefin multi-block copolymers, and combinations thereof.

5. The article according to any one of claims 1 to 4, wherein The ethylene polymer is a native ethylene polymer before the cross-linking composition is cross-linked; and The cross-linked composition has (i) a storage modulus value G' at 140°C, which is greater than the storage modulus value G' of the native ethylene polymer at 140°C; (ii) a tan δ value at 60°C that is less than the tan δ value at 60°C of the native ethylene polymer; and (iii) a tan δ value at 140°C that is less than the tan δ value of the native ethylene polymer at 140°C.

6. A product comprising: An extruded profile composed of a cross-linked composition comprising: Ethylene polymers; and Bonds with structure 2 7. A method comprising: The first article is heated to a reprocessing temperature, wherein the first article is composed of an extruded profile, the extruded profile is composed of a cross-linked composition, and the cross-linked composition comprises: (i) ethylene polymers; and (ii) Bonds of Structure 2 forming the first article into a reprocessable ethylene polymer composition at the reprocessing temperature; forming the reprocessable ethylene composition into a reprocessable preform at the reprocessing temperature; as well as The reprocessed preform is cooled to below the reprocessing temperature and forms a second article comprised of a recrosslinked ethylene polymer composition comprised of: (i) the ethylene polymer and (ii) bonds having Structure 2.